2010
DOI: 10.1111/j.1475-2743.2010.00286.x
|View full text |Cite
|
Sign up to set email alerts
|

Compost can successfully replace mineral fertilizers in the nutrient management of commercial peach orchard

Abstract: The objective of this experiment was to evaluate in the long-term (9 years), the suitability of compost as a fertilizer in commercial peach orchard. The experiment was carried out on nectarine trees (Prunus persica var. nectarina), Stark RedGold grafted on GF677 peach · almond (P. amygdalus L.) hybrid. The treatments were: (1) unfertilized control; (2) mineral fertilization including phosphorus (P at 100 kg ⁄ ha) and potassium (K at 200 kg ⁄ ha) applied at planting and nitrogen (N at 70-130 kg ⁄ ha ⁄ yr) split… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
2
11

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 23 publications
5
47
2
11
Order By: Relevance
“…These results can be explained by higher dry matter production of crops in the treatments with manure applications , as well as the use of no-tillage during the experiment, which provided an increase in levels of soil organic matter, as observed by Lourenzi et al (2011). This is because total N is closely related with the levels of soil organic carbon (SOC), as stated by Baldi et al (2010). These authors, studying different nutrient sources for eight years, observed that increased SOC promoted an increase in total N, with a correlation of 94 %.…”
Section: Resultsmentioning
confidence: 61%
“…These results can be explained by higher dry matter production of crops in the treatments with manure applications , as well as the use of no-tillage during the experiment, which provided an increase in levels of soil organic matter, as observed by Lourenzi et al (2011). This is because total N is closely related with the levels of soil organic carbon (SOC), as stated by Baldi et al (2010). These authors, studying different nutrient sources for eight years, observed that increased SOC promoted an increase in total N, with a correlation of 94 %.…”
Section: Resultsmentioning
confidence: 61%
“…Em mangueiras 'Tommy Atkins'adultas, cultivadas em sistema orgânico irrigado no semiárido brasileiro, Silva et al (2013) concluíram que a produção e o número de frutos por planta foram maiores com adubos orgânicos provenientes de compostos enriquecidos com MB4 ® e termofosfato, que apresentaram maiores concentrações totais de nutrientes. Em um trabalho conduzido durante 8 anos no Vale do Po, na Itália, realizado com nectarineiras 'Stark RedGold', os rendimentos em produção aumentaram de 13,5 t ha -1 para 19,9 t ha -1 em função do aumento de doses de adubo orgânico, da matéria orgânica do solo e da maior disponibilidade de nutrientes N, P e K no solo (BALDI et al, 2010;TOSELLI, 2010). Por outro lado, em nectarineiras 'Orion'cultivadas em potes por dois anos, Bravo et al (2012) relatam que a aplicação de adubo orgânico na forma de composto, constituído por material de poda de árvores urbanas e resíduos orgânicos domésticos, aumentou a fixação de 13 CO 2 , promovendo o crescimento da parte aérea e raízes das nectarineiras, mas não afetou a biomassa dos frutos nem a absorção de nitrogênio.…”
Section: ----------------------------------------Mm -----------------unclassified
“…Além disso, a aplicação do material orgânico induziu o aumento da atividade microbiana no solo e os teores de macro e micronutrientes, assim como a liberação de N inorgânico. Efeitos positivos da adubação orgânica também foram reportados para outras frutíferas como nectarineiras (BALDI et al 2010;TOSELLI, 2010) e mangueiras (SILVA et al, 2013).…”
Section: Introductionunclassified
“…Entre os melhores produtos, os compostados mistos, por acessibilidade, custo e qualidade, são preferíveis quando o esterco não é disponível. A partir de experimentos conduzidos com pessegueiro (BALDI et al, 2010) foi observado que o aporte de 10 toneladas de matéria seca/ha/ano de composto misto determina um aumento da M.O. no solo de aproximadamente 1% no período de 5 anos.…”
Section: A Adubação Na Fase De Pré-plantiounclassified
“…do solo de um pomar de pessegueiros adultos cv Stark Red Gold/GF 677 em Ravenna, IT. Baldi et al (2010).…”
Section: A Adubação Na Fase De Pré-plantiounclassified